LoRaWAN-Based Fishing Zone Violation Monitoring System for Traditional Fishing Vessels in the Malacca Strait - Enda, Depandi; Kurniati, Rezki; Kumara, I Made Surya (Politeknik Negeri Bengkalis, 2024)
The fisheries and marine sectors are among the potential sectors that Indonesia possesses. Fishermen, as theprimary drivers of the maritime field, play an important role in the country's economy. As a sovereign nation, thegovernment is expected to ensure and protect the safety of fishermen, particularly traditional fishermen who carry outfishing activities in Indonesian territorial waters. However, there are still many issues encountered in the field. One of themis the violation of fishing zones by traditional fishing vessels. With the numerous cases of fishing zone violations occurring,at least two main factors contribute to these violations: the lack of information regarding the permitted fishing zones thatare still within Indonesia's territorial waters and the limited availability of navigation tools such as GPS and AIS, whichmany fishermen do not possess, preventing them from accurately knowing their position while fishing and whether theyhave exited the permitted zones. A fishing zone violation monitoring system is greatly needed to provide solutions to thisproblem. This study aims to design a monitoring system for fishing zone violations by traditional fishing vessels usingLoraWAN technology as a communication device. The designed system will automatically provide early warnings fromthe Lora-Gateway to traditional fishermen who are fishing outside the designated zones through the Lora-Transponderdevice installed on the fishing vessels. The system will monitor every movement of vessels violating the fishing zone byutilizing the mapping data of Fishing Zone coordinates, stored in a real-time coordinate database. The monitoring systemwill also automatically send notifications as an early warning system if there are traditional fishing vessels that exit thelegally established fishing zones by the government, referring to Indonesia's Exclusive Economic Zone (ZEE) of 200nautical miles from the baseline coast. With this real-time monitoring system, it is expected to assist government agenciesand stakeholders in monitoring the fishing activities of traditional fishing vessels, especially in the Malacca Strait region.